Menopause and COVID19 severity: The missing link - Ruby Dhar; Arun Kumar; Subhradip Karmakar (Asian Journal of Medical Sciences, 2021)
COVID-19 pandemic has far-reaching consequences on people with comorbidities like Diabetes Mellitus (DM), asthma, cardiovascular disease, and cancer. What seems unusual is an isolated observation that emerged from several independent studies worldwide. Postmenopausal females seem to suffer from severe COVID symptoms. Few of them also show an extended COVID symptom, also “LONG COVID.” Though the association appears strong, there are not enough credible studies to pin it down to the exact cause. We explored the possibility to see if postmenopausal females are at a higher risk for severe COVID and unravel this observation’s molecular pathogenesis.